2015
DOI: 10.1155/2015/536041
|View full text |Cite
|
Sign up to set email alerts
|

Association of Angiotensin Converting Enzyme Insertion-Deletion Polymorphism with Hypertension in Emiratis with Type 2 Diabetes Mellitus and Its Interaction with Obesity Status

Abstract: The association of Angiotensin Converting Enzyme (ACE) insertion-deletion (I/D) polymorphism with Type 2 Diabetes Mellitus (T2DM) and hypertension has been extensively studied throughout various ethnic populations but largely with inconsistent findings. We investigated these associations in Emirati population and their interaction with obesity status. Saliva samples were collected from a total of 564 Emiratis (277 T2DM and 297 healthy). DNA was extracted and the samples were genotyped for ACE I/D polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
5
14
0
Order By: Relevance
“…ACE genotype distribution differs from one population to another or even from one year to another in the same population. In Palestine, the D/D genotype was the most frequent genotype as demonstrated by the present study and this result is also similar to other studies [8,12], as it was shown to be the most frequent genotype in Iraq [13], while the I/D genotype was the most frequent genotype in Turkey [14] and the UAE [6]. Some countries like Egypt [15,16] have an inconstant frequency for the genotypes, and this may be related to the sample size, the population of the study or the techniques used in the determination of ACE gene polymorphism.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…ACE genotype distribution differs from one population to another or even from one year to another in the same population. In Palestine, the D/D genotype was the most frequent genotype as demonstrated by the present study and this result is also similar to other studies [8,12], as it was shown to be the most frequent genotype in Iraq [13], while the I/D genotype was the most frequent genotype in Turkey [14] and the UAE [6]. Some countries like Egypt [15,16] have an inconstant frequency for the genotypes, and this may be related to the sample size, the population of the study or the techniques used in the determination of ACE gene polymorphism.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of the association with HTN, it was not deemed to be statistically significant, and this result concurs with [8] and [14] but disagrees with Alsafar et al (2015) [6]. D/D genotype…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations